Precision medicine research progress based on colorectal cancer organoids - Xiyou Pang; Yuqing Hu; Zhihui Dai; Qiuwen Lou; Wenxia Xu; Lin Chen (Discover Oncology)
Abstract Organoids are cultures that use stem cells to induce differentiation or clinical samples as raw materials to form three-dimensional spatial structures through specific culture systems, thereby simulating the structure and function of tissues in vivo. Organoids are characterized by their ease of construction, long-term stable passage, clinical authenticity, and application in high-throughput drug screening. Patient-derived organoids have great application value in colorectal cancer research and individualized treatment. In this review, recent advances in colorectal cancer organoid culture technology, clinical individualized drug sensitivity assessment, new drug screening, drug mechanism research, nanomedicine-based applications, and imaging technology are summarized. These advancements will provide support for the precise diagnosis and treatment of colorectal cancer and the development of new treatment strategies, which will have significant scientific value and clinical transformation value.